Hubungan Antara Burnout dengan Motivasi Berprestasi pada Karyawan PT. X di Samarinda - Meissy Bella Sari; Arundati Shinta; FX Wahyu Widiantoro (LPPM Universitas Proklamasi 45, 2022)
This research is motivated by one of the problems faced by each company regarding the quality of human resources (HR) which is the key to all development efforts in all fields. This new phenomenon shows that human resources, in this case employees, have not been able to work optimally within the company, whereas the progress or decline of the company will be seen from the skills and performance of the people in the company. Because its role to implement strategy is very important, namely as the executing subject of organizational strategy. One way that a company or organization can do is by properly managing and developing its employees so that the company can work effectively and efficiently. This research is a quantitative descriptive study with a sample size of 30 respondents, while the sampling technique used in the study was purposive sampling. In this study, the independent variable is burnout, while the dependent variable is achievement motivation. Testing instruments using validity and reliability tests with the product moment from Karl Pearson. While the data analysis method used descriptive analysis, classical assumption test and Pearson correlation analysis. The results showed that there was a negative and significant relationship between the burnout variable and achievement motivation as evidenced by the hypothesis using bivariate analysis (r = -0.521, p < .05). We conclude that the high burnout correlate with the low achievement level among the PT. X employees in Samarinda.